2004
DOI: 10.1002/adsc.200404126
|View full text |Cite
|
Sign up to set email alerts
|

Proline‐Derived N‐Sulfonylcarboxamides: Readily Available, Highly Enantioselective and Versatile Catalysts for Direct Aldol Reactions

Abstract: Proline catalysis of the asymmetric direct aldol reaction involves both the secondary amine function and the carboxyl group of the amino acid. N-Sulfonylcarboxamides are known to be of similar acidity as carboxylic acids, and three N-arylsulfonyl derivatives of l-proline amide were synthesized as functionalized and versatile derivatives of l-Pro. Their catalytic performance was evaluated in the direct aldol addition of acetone to 4-nitrobenzaldehyde. Significantly improved reactivities and enantioselectivities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
78
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(85 citation statements)
references
References 34 publications
5
78
0
2
Order By: Relevance
“…The corresponding N-tosylcarboxamide has been reported to promote the aldol reaction of acetone with p-nitrobenzaldehyde in an organic solvent to afford the product with excellent enantioselectivity. [33] The length of the alkyl chain had a significant effect on the yield. The organocatalyst with an octylsulfonyl moiety, 6 a, produced a good yield with excellent diastereo-and enantioselectivities, while that with the dodecylsulfonyl moiety, 6 b, provided a low yield albeit with excellent selectivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding N-tosylcarboxamide has been reported to promote the aldol reaction of acetone with p-nitrobenzaldehyde in an organic solvent to afford the product with excellent enantioselectivity. [33] The length of the alkyl chain had a significant effect on the yield. The organocatalyst with an octylsulfonyl moiety, 6 a, produced a good yield with excellent diastereo-and enantioselectivities, while that with the dodecylsulfonyl moiety, 6 b, provided a low yield albeit with excellent selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…carboxyamide moiety 6 were synthesized by reaction of the 4-nitrophenyl ester of Z-proline 10 with the appropriate sulfonylamides to give 11, followed by hydrogenolysis [33] (Scheme 3). The trans-siloxy-l-proline catalysts 7 a-c were prepared by first treating the benzyl ester of Z-4-hydroxyproline with the appropriate silyl chlorides and imidazole to give 12 a-c, followed by hydrogenolysis (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…anti/syn [c] ee First, we examined proline Nsulfonyl amides 6 and 7 containing long alkyl chains (Scheme 1). Though similar N-arylsulfonyl amides are excellent aldol catalysts in organic solvents, as reported by Berkessel et al [11] and Ley and coworkers, [9] 6 and 7 were found to be poor catalysts: an emulsion did not form in the reaction mixture, and the products were obtained in low yield. Next, we developed the novel catalysts 8-13, which contain both a proline unit and a long alkyl chain and which were easily prepared in large quantities from commercially available l-4-hydroxyproline.…”
mentioning
confidence: 79%
“…Although organocatalysts like proline have many attractive features, this catalytic system also suffers from some demerits like high catalyst loading or poor solubility in organic solvents. To overcome these problems many groups have tried to replace proline with other amino acids [15,16]. Consequently, a various proline mimetics have been synthesized to improve reactivity such as tetrazole [11,17a], prolinamides [17b], sulfonamides [17a,18] as well as derivatives of 4-trans hydroxyproline [19].…”
Section: Introductionmentioning
confidence: 99%